Ilmu Metafisika Ibnu Rusyd dan Kontribusinya terhadap Umat Islam di Timur dan di Barat - Rabiya Al Adawia; Syaidil Khudri; Muhammad Kahfiki Marulafau; Indra Pratama; Fadhlan Kamali Batubara (ANWARUL, 2025)
Although the intellectual works of the Muslim thinker Ibn Rushd have attracted considerable scholarly attention, studies that specifically examine his metaphysical concepts and their contribution to Islamic thought in the East and the West remain limited. This study aims to analyze Ibn Rushd’s concept of metaphysics, particularly the relationship between reason and revelation, and its influence on the development of philosophical thought in the Western world. The research employed library study (library research) with a qualitative-descriptive approach through analysis of Ibn Rushd’s primary texts and relevant secondary literature. The findings show that Ibn Rushd’s ideas affirm the central role of reason in understanding existence, strengthen the tradition of critical thinking, and constitute one of the foundations for the development of scholastic philosophy and rationalism in Europe. The study concludes that Ibn Rushd’s metaphysical thought is not only significant within the context of Islamic philosophy, but also functions as an intellectual bridge between Islamic and Western traditions of thought, helping to pave the way for the intellectual renaissance in Europe. The implications of this research include a theoretical contribution to enriching the literature on metaphysics, as well as practical implications for readers in deepening their understanding and application of metaphysical principles in life, while also opening opportunities for further exploration of the importance of accepting and developing rational ideas in contemporary Islamic philosophical studies.